Adopting blockchain in supply chain: A methodological proposal to conduct a pilot - Tokkozhina, U. (2021)
The world nowadays and business processes, in particular, are changing to-wards digitalization and reduction of time-consuming processes. Provenance and safety of products are becoming key factors for customers’ trust, so traceability solutions are arising. One of the most up-and-coming disruptive technologies today is a Blockchain (BC). This paper aims to assess the feasi-bility of BC to enable end-to-end supply chain (SC) and to develop a tenta-tive methodological framework of the BC level of success in SC context evaluation. The pilot shows that BC provides convenience in using a unified information system for different stakeholders throughout SC for more effi-cient and secure data exchange. A future understanding of the importance for BC technology use, as a traceability provider from the perspective of a final customer, is detected as a path for further research.